Veronika, dkk PENGARUH RESPON TENTANG MEDIA VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR MATERI LARUTAN ELEKTROLIT NON ELEKTROLIT SMA GELEKAT LEWO BORU TAHUN 2020/2021 - Tinenti, Yanti Rosinda; Tukan, Veronika D. L.; Lawung, Yustina D. (Jurnal Riset Pendidikan Kimia (JRPK), 2024)
The main objectives of this study are (1) to determine the validity of the learning video media for electrolyte and non-electrolyte solutions. (2) Knowing the response of students about learning videos on electrolyte and non-electrolyte solution materials. (3) Knowing the learning outcomes of students who use learning videos on electrolyte and non-electrolyte solutions. (4) Knowing the relationship of students' responses to learning video media on student learning outcomes after using learning videos on electrolyte and non-electrolyte solution materials. (5) Knowing the effect of student responses on learning video media on student learning outcomes after using learning videos on electrolyte and non-electrolyte solution materials. Based on the results of data analysis and discussion, it can be concluded that (1) The validation of the learning video media is declared valid with a validity value of 92.5. (2) The responses of class X IPA students at SMA Geangkat Lewo Boru for the Academic Year 2020/2021 are included in the very good category with an average percentage of 83%. (3) The learning outcomes of class X IPA students at SMA Geangkat Lewo Boru for the Academic Year 2020/2021 were declared complete with an average score of 85. (4) There was a significant relationship between responses and student learning outcomes. students of class X science at Geangkat Lewo Boru High School for the 2020/2021 academic year with a correlation coefficient of 0.55 (5) There is a significant effect between the response and learning outcomes of students in class X science at Gelekat Lewo Boru School Year 2020/2021 with a simple regression equation of Y = 57.64 + 0.33x.